Image segmentation using active contours with image structure adaptive gradient vector flow external force - Wang, Dong; Dang, Xing; Liu, Weijing; Wang, Yuanquan (Frontiers in Applied Mathematics and Statistics, 2023)
The gradient vector flow (GVF) has been proven as an effective external force for active contours. However, its smoothness constraint does not take into account the image structure such that the GVF diffusion is isotropic and cannot preserve weak edges well. In this article, an image structure adaptive gradient vector flow (ISAGVF) external force is proposed for active contours. In the proposed ISAGVF model, the smoothness constraint is first reformulated in matrix form, and then the image structure tensor is incorporated. Since the structure tensor characterizes the image structure well, the proposed ISAGVF model is able to be adaptive to image structure, and the ISAGVF snake performs well on weak edge preserving and deep concavity convergence while possessing some other desirable properties of the GVF snake such as enlarged capture range and insensitivity to initialization. Experiments on synthetic and real images manifest these properties of the ISAGVF snake.